Rakebot: a robotic rake for mixing paddy in sun drying - Ertie Cusipag Abana; Meljiflor Pacion; Roxanne Sordilla; Daniel Montaner; Dennis Agpaoa; Rryma Mae Allam (Institute of Advanced Engineering and Science, 2019)
Sun drying is a conventional drying method of paddy commonly used in Asia. During the process, grains are mixed and turned continuously using a rake to maintain good quality. For this reason, a robotic rake or Rakebot was developed in this study to properly mix the grains during sun drying. Rakebot is manually controlled using a mobile application through Bluetooth connection but can also move automatically using the previous movements that were recorded on the first used. It was developed using a microcontroller that gives directions to the motors based on the received instructions from the mobile application. The recorded movements are saved in a memory card by means of a memory card module connected to the microcontroller. The objective measures showed that the Rakebot ensures simultaneous reduction of the moisture content of paddy. Also, the rake design of the robot prevents fissuring of grains.